Increasing Psychological Well-Being Through Role Awareness Training Among Student-Athletes in National Potential Young Athlete Training Center - Miftakhul Jannah; Riza Noviana Khoirunnisa; Satiningsih Satiningsih; Siti Jaro'ah; Rachman Widohardhono; Andi Ledy Permata Putri; Nabila Rachman; Muhammad Aufa Al Farisi Ann Haba Sauda (IJORER : International Journal of Recent Educational Research, 2024)
Objective: In response to the problem of the dual career of student-athletes during quarantine resulting in a psychological well-being crisis. This study aims to assess the effect of role awareness training developed to improve the psychological well-being of student-athletes. The study aims to determine the effect of role awareness training on psychological well-being in student-athletes at the National Potential Young Athlete Training Center. Method: A quantitative experimental method with a pretest-posttest control group design was used. The subjects of this research were 24 athletes of the National Young Athlete Training Center. Sampling is done with a saturated sample, where all population members become a sample. Data was obtained through pretest and posttest using a psychological well-being instrument that contains 42 items. JASP (Jeffrey’s Amazing Statistics Program) for Windows software was used to analyze the data used in the study. The data analysis technique used was the independent sample t-test. Results: The results showed that role awareness training can guide athletes in improving psychological well-being. Novelty: In response to the problem of the dual career of student-athletes during quarantine resulting in a psychological well-being crisis. This research concludes that role awareness training influences psychological well-being in student-athletes.